Sustainable Competitiveness Amid China-US Trade Frictions: A Case Study of ZTE - Jiarui Hou; 이훈숙; 최명철; 김한얼 (International Journal of Advanced Culture Technology(IJACT), 2025)
In the complex backdrop where globalization and geopolitics intersect, China-US trade frictions have not only profoundly impacted the global economic landscape but also presented unprecedented challenges to the enterprises involved. ZTE Corporation, as one of the leading companies in China's communication industry, has drawn particular attention for its digital transformation strategy in this broader context. This paper delves into ZTE's response measures and transformation paths amid China-US trade frictions, aiming to reveal how it copes with external uncertainties through internal management and technological innovation, as well as the achievements and challenges encountered in this process. This paper employs SWOT analysis to comprehensively evaluate ZTE's market competitiveness and financial health amid ongoing trading tensions between China and the United States. In the face of trade sanctions imposed by the U.S. government and severe market challenges, ZTE has effectively mitigated the negative impacts of these sanctions by accelerating digital transformation, strengthening compliance management, enhancing its independent research and development capabilities, and reinforcing its leadership in key technological areas such as 5G and cloud computing. The ZTE has successfully improved its market competitiveness and financial performance through continuous innovation and transformation despite the difficulties of China-US trade friction.